Penggunaan Sapaan Pedagang Makanan di Lingkungan Kampus - Erfiani Baroroh, Hilma (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2022)
This research is a sociolinguistic study conducted in a simple scope of a campus setting. It aims at understanding the pronominal address system that is used in business conversational settings between sellers-buyers and canteen owners and their employees, as well as the responses from the speakers i.e. both the buyers and canteen employees. The theory used to achieve the goal is Brown and Gilmanâ€™s theory of pronominal address forms (1972). The analysis on the seven ways used by sellers in addressing (1) students; (2) security officers; (3) sellers from their own/same hometown; (4) sellers from different hometowns; (5) parking attendants; (6) photocopy employees; and (7) cleaning service employees, revealed that â€˜addressing by name onlyâ€™ was used to address younger people that the sellers had known already, as well as for addressing people whom they considered close, while the words â€œMasâ€ (brother), â€œMbakâ€ (sister), Ibu (madam), and Bapak (mister) were used for addressing older people as honorific titles that are deemed more respectful. The findings confirmed one of the Indonesiansâ€™ typical â€œEasternâ€ values, which is the use of specific pronominal address words in day-to-day lives. Penelitian ini merupakan penelitian dalam bidang sosiolinguistik, yang dilakukan di ruang lingkup yang sederhana yaitu di lingkungan kampus. Penelitian ini berusaha mengungkapkan sistem sapaan yang digunakan pada tuturan seputar kegiatan perdagangan, antara penjual-pembeli maupun antara pemilik kantin dengan pegawainya dan respon yang diberikan oleh petutur, baik itu pembeli maupun pegawai kantin. Teori yang digunakan untuk mencapai tujuan tersebut adalah teori tutur sapa Brown dan Gilman (1972). Dari tujuh analisis penggunaan sapaan pedangang kepada (1) mahasiswa; (2) satpam; (3) sesame pedagang sedaerah; (4) sesama pedagan lain daerah; (5) petugas parkir; (6) petugas fotokopi; dan (petugas cleaning service), ditemukan panggilan â€œnamaâ€ sapaan bagi yang lebih muda karena sudah mengenal dan sebagai sapaan langsung secara akrab, dan panggilan â€œMasâ€, â€œMbaâ€, â€œIbuâ€, dan â€œBapakâ€ bagi yang lebih tua karena untuk lebih menghormati. Hal ini sejalan dengan ciri khas budaya ketimuran orang Indonesia dan kata sapaan yang digunakan dalam kehidupan sehari-hari.